Bone mineral density of endurance-trained male athletes : pathophysiology of exercise-induced osteopenia - Prins, Hendrina Catherina (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Nutrition) -- University of Stellenbosch, 1996.